Optimizing the quantification of the pine wood nematode (Bursaphelenchus xylophilus) in Pinus pinaster through real-time quantitative PCR - Gouveia, Virgilio Pires (2021)
Mestrado em Engenharia Agronómica - Proteção de Plantas / Instituto Superior de Agronomia. Universidade de Lisboa